CONNECTION WITHOUT CONJUNCTIONS IN BAHDINI KURDISH COMPOUND SENTENCES: لێگدانا بێ ئامراز درستا لێکدایا گۆڤەرا بەهدینیا زمانێ کوردیدا - Ahmed, Bayez Omer (Journal of Duhok University, 2018)
When analyzing discourse or text into paragraphs, and paragraphs into sentences, the big problem is to identify those compound sentences without conjunctions. This study aims at identifying types of connection without conjunctions in Bahdini Kurdish sentences, depending on descriptive analytical approach